Aquatecture of a city park: A methodological experiment in the design process for Belgrade Linear Park - Stojković Minić, Miloš (Arhitektura i urbanizam, 2021)
The aim of this paper is to interpret the term Aquatecture in the design process for Zone 8 of Belgrade Linear Park, as a case study for understanding the concept and methodology used, as well as their application in operational architectural and urban practice. The paper describes the methodological procedure applied to structuring the space using water, with the aim of designing ambiences inspired by nature. This methodological experiment is illustrated with graphical representations of the process itself, in which the colors and shapes of water are analyzed through the observation of water droplets under the microscope. The research hypothesis is that one drop of water contains information important for architectural activities, and therefore the research offers a set of procedures and methods that can be applied and controlled through the creative act of coloring and shaping, or more precisely the creation of Spatial Images. The methodological procedure in the research can be described as poetic and artistic, at the same time containing a scientific element in the analysis and observation of the water sample under the microscope. All other visual perceptual observations and results in the interpretation of the observed environment and the water droplets, as well as their colors and shapes, are offered as extremely intuitive. The research is presented in the form of a Tableau consisting of seven parts and a set of photographs, drawings and images, as well as tone maps (color palette), according to which the results are applied through Spatial Images. Spatial images are interpreted as Ambience inspired by nature, at a specific location: Zone 8 of Belgrade Linear Park, as a case study for researching this methodological procedure. The data obtained in this way is applied in the structuring of the park’s aquatecture and pavilions. The waterflows in the park itself are explained in the text, as well as the spatial structures such as the landscape fountain on the square and the main park pavilion itself, which is interpreted as a one-of-a-kind House of water. Therefore, as a product of the work, an environmental project inspired by nature is offered as the Aquatecture of Zone 8 in Belgrade Linear Park, illustrating the practical application of water as a methodological tool, and an inspiration in the processes of architectural design and water space structuring. In this way, the case study of the Conceptual Architectural and Urban Design of Zone 8 of the Linear Park in Belgrade offers new interpretations and understandings of Aquatecture in Belgrade in professional practice. More precisely, it re-examines ways of applying and understanding the concepts of the Blue Green Dream (BGD) and Nature Based Solutions (NBS) in shaping public spaces in the city.